Prolactinomas in adolescent and elderly patients—A comparative long-term analysis - Andereggen, Lukas; Tortora, Angelo; Schubert, Gerrit A.; Musahl, Christian; Frey, Janine; Luedi, Markus M.; Mariani, Luigi; Beck, Jürgen; Christ, Emanuel (Frontiers in Surgery, 2023)
Objectives: Prolactinomas represent the most common type of secreting pituitary adenomas, yet are rarely encountered in adolescent-onset (AO; i.e. <18 years) or elderly-onset (EO; i.e. ≥ 65 years) cohorts. As a result, it is not clear whether long-term strategies should be focused differently at both age extremes when comparing their therapeutic outcomes. We aimed at investigating long-term endocrinological outcomes, looking for differences between the two cohorts and evaluating the dependence on continued dopamine agonist (DA) therapy. Methods: Retrospective cross-sectional comparative study analyzing prolactinoma patients with a follow-up of ≥4 years. Clinical, radiological and biochemical characteristics were assessed at diagnosis and last follow-up. Longitudinal endocrinological outcomes between groups of extreme ages (i.e. AO and EO) and middle age (i.e. ≥18 years to 65 years) were compared. Independent risk factors for long-term dependence on DAs were calculated. Results: Follow-up at ≥4 years was recorded for 108 prolactinoma patients; 10 patients with AO and 10 patients with EO. Compared to AO patients, EO patients were predominantly men (p=0.003), and presented with significantly higher prolactin (PRL) levels (p=0.05) and higher body mass index (p=0.03). We noted a significant positive correlation between patients’ PRL values and their age (r=0.5, p=0.03) or BMI (r=0.6, p=0.03). After a median follow-up of 115 months, remission was noted in 87 (83%) patients; 9 (90%) in AO patients, and 7 (70%) in EO patients (p=0.58). Continuation of DAs was required in 4 patients (40%) with AO and 7 patients (70%) with EO (p=0.37). Patients with elderly-onset were an independent predictor of long-term dependence on DAs (HR 2.8, 95% CI 1.1-7.2, p=0.03). Conclusions: Long-term control of hyperprolactinemia and hypogonadism does not differ between members of the AO and EO cohorts, and can be attained by the majority of patients. However, adjuvant DAs are often required, independent of the age of onset. Considering the clinical significance of persistent DA therapy for the control of hyperprolactinemia in many patients at both extremes of age, long-term monitoring may become recommended, in particular in patients with elderly-onset.